The Grammaticalization of Bipartite Reciprocal Markers in Hebrew - Halevy, Rivka (Hebrew studies, 2011)
Grammaticalization is generally viewed as a diachronic process of: lexical > grammatical and grammatical > more grammatical. This paper deals with the grammaticalization of bipartite reciprocal markers in Hebrew as a striking example of a process whereby lexically meaningful morphemes are gradually emptied of their content and become "function" elements (i.e., reciprocal pro-Nouns), forming an evolutional continuum from a less grammaticalized (i.e., less fossilized) category into a more grammaticalized one (i.e., that of bipartite reciprocal markers). It is argued here that Hebrew is notable in that its bipartite reciprocal markers demonstrate a less advanced stage of grammaticalization than their counterparts in many languages worldwide.